Ethical Considerations in Screening for Rapid Eye Movement Sleep Behavior Disorder in the General Population - Dommershuijsen, Lisanne J.; Darweesh, Sirwan K.L.; Luik, Annemarie I.; Kieboom, Brenda C.T.; Koudstaal, Peter J.; Boon, Agnita J.W.; Ikram, M. Arfan; Ikram, M. Kamran; Bunnik, Eline M. (Movement disorders, 2020)
ABSTRACT Clinical studies have shown that up to 90% of patients with idiopathic rapid eye movement sleep behavior disorder (RBD) will eventually be diagnosed with a clinical α‐synucleinopathy. Because of this high conversion rate, screening for RBD is often performed to identify eligible participants for studies aimed at elucidating the prodromal phase of α‐synucleinopathies. However, screening for RBD, especially in the general population, raises many ethical dilemmas. In light of the existing ethical literature and our experience in establishing a screening approach for RBD in the Rotterdam Study, we discuss ethical dilemmas when screening for RBD in population‐based studies. We conclude that informing study participants about the reason for invitation and the possible trajectory that lies ahead when participating is essential. However, participants should not be troubled unnecessarily by giving them detailed information about possible diagnoses or associated disease risks. © 2020 International Parkinson and Movement Disorder Society